The quality of Neuer Markt quarterly reports: An empirical investigation - Anne D'Arcy; Sonja Grabensberger (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2002)
For the Neuer Markt year 2001 is not considered as one of its best, compared to its prior performance. Investors who once piled into the Neuer Markt have now become wary of the exchange, which was launched in 1997 as Europe's leading growth market and answer to the U.S.`s Nasdaq Stock Market. The Neuer Markt's reputation has been marred by the misleading information policy from several Neuer Markt companies, publishing false annual and quarterly data. Some of these companies are responsible for having misinformed investors of their pending bankruptcies. Under these circumstances, it is time to find an explanation for the dramatic loss of credibility in Neuer Markt enterprises. Finding an answer, two aspects come under consideration: What type of information (annual versus quarterly reports) was available for investors and of what quality were these provided data. Interim reports can be seen as important instrument in the reporting system to inform all kinds of investors. For this reason we examine the quality of Neuer Markt quarterly reports by concentrating on the disclosure level of 52 Neuer Markt companies` reports for the third quarter 1999 and 2000. To enable comparison we establish four disclosure indexes that measure the report's compliance with the Neuer Markt Rules and Regulations as well as with IAS and US GAAP interim reporting standards. The results demonstrate that the level of disclosure has increased over time. Then we aim to find typical attributes of Neuer Markt enterprises that provide high or low level of accounting information in their quarterly reports. Nevertheless the study also shows that there is not any correlation between market capitalization and the quality of interim reports. However, it can be suggested that an additional enforcement mechanism could improve quality and lure investors back. A step towards this aim is the standardization project of quarterly reports of Deutsche Boerse AG.
urn:nbn:de:hebis:30-18071
Keywords: 330; Geschäftsbericht; Öffentlichkeitsarbeit; Informationswert; Bilanzierungsgrundsätze; IFRS; Deutschland; New Economy